Role of miRNA in the development of atrial fibrillation in patients with valvular heart disease - I. V. Abdulyanov; N. B. Amirov; M. R. Gaisin; A. E. Kaipov; A. I. Abdrakhmanova (Кардиоваскулярная терапия и профилактика)
Atrial fibrillation (AF) is a common type of arrhythmia that is frequently observed in clinical practice. In patients admitted to the cardiac surgery department, AF most often develops due to valvular heart disease, as well as in the postoperative period. Modern surgical techniques for valvular defects make it possible to get rid of AF. However, there are still unresolved issues of treatment tactics, the selection of procedure and the correct selection of patients for surgery. In order to find answers to these questions, the influence of microribonucleic acids (miRNAs) on the development and course of AF is being studied. The article presents an analytical review on the influence of miRNA on the occurrence, regulation and course of AF in patients with valvular heart disease before surgery and in the postoperative period.